Last days in Cleaver Square - McGrath, Patrick 1950- (Hutchinson, 2021)
It is 1975 and an old man, Francis McNulty, a veteran of the Spanish Civil War, is beset with sightings in his garden of his old nemesis, General Franco. The general is in fact in Spain, on his deathbed, but Francis is deeply troubled, as is his daughter Gillian, who lives with him in Cleaver Square. Francis' account of his haunting is by turns witty, cantankerous and nostalgic. At times he drifts back to his days in Madrid, when he rescued a young girl from a burning building and brought her back to London with him. There are other, darker events from that time, involving an American surgeon called Doc Roscoe, and a brief, terrible act of betrayal. When Gillian announces her forthcoming marriage to a senior civil servant, Francis realizes he has to adapt to new circumstances and confront his past once and for all. Highly atmospheric, and powerfully dramatic, rich in pathos and humour, Last Days in Cleaver Square confirms a major storyteller at the height of his powers. '[W]onderfully sinister ... a delight ... you are in for a thrilling ride.' Spectator on The Wardrobe Mistress
Keywords: Veterans / Fiction; Fathers and daughters / Fiction; Spain / History / Civil War, 1936-1939 / Participation, Foreign; Historical fiction